Single vs. double purse-string anastomosis during laparoscopic low anterior rectal resection (SINGLE–DOUBLE trial): study protocol for a randomized controlled trial - Xiaolan You; Jian Wu; Yuanjie Wang; Qinghong Liu; Dehu Chen; Xiaojun Zhao; Yan Zhou; Xiaoqing Wu; Daorong Wang (Trials, 2019)
Abstract Background An inappropriate anastomosis method during laparoscopic anterior rectal resection can increase the risk of anastomotic complications and affect surgical, economic, and oncological outcomes. The aim of this study is to compare the incidence of anastomotic complications and the surgical, economic, and oncological outcomes following single versus double purse-string anastomosis during laparoscopic total mesorectal excision (TME) for low rectal cancer. Methods/design This randomized controlled trial (the SINGLE–DOUBLE study) will randomly assign middle and low rectal adenocarcinoma patients to receive either single or double purse-string anastomosis during laparoscopic low anterior rectal resection. Patients will be eligible for inclusion only if they (1) have adenocarcinoma confirmed by preoperative colonoscopy and biopsy, (2) have a tumor situated less than 12 cm from the anal verge, (3) do not have the anal sphincter involved, and (4) do not have distant metastases. The primary endpoint measure will be the incidence of anastomotic complications (leakage, narrowing, and bleeding). The secondary endpoints will be surgical, economic, and oncological outcomes. A total of 500 patients will be enrolled in the study. Sample size calculation was based on previous reports and our retrospective analysis. Discussion This randomized single-center controlled trial is expected to demonstrate which anastomosis method (single or double purse-string anastomosis) is better for reducing complications and improving prognosis in rectal cancer patients undergoing laparoscopic TME for low or middle rectal cancer. Trial registration Registration number: ChiCTR1800016116. Protocol Registration Receipt: May 13, 2018.